Compulsory Land Acquisition and Voluntary Land Conversion in Vietnam : The Conceptual Approach, Land Valuation and Grievance Redress Mechanisms - World Bank (World Bank, Hanoi, 2017)
This publication is the product of a multi-year cluster analytical and advisory work on social and land conflict management of the World Bank office in Hanoi, which aimed to assist Ministry of Natural Resources and Environment (MoNRE) to improve the land acquisition and conversion process to achieve more sustainable development during the current rapid urbanization and industrialization process. There are three reports explained in this study as: 1) the policy note on improving land acquisition and voluntary land conversion in Vietnam; the study on land valuation mechanisms for compensation, support and resettlement in Vietnam; and the study on improving the system for resolving complaints on compensation, support and resettlement in Vietnam. The objective of the study was to assess the issues relating to involuntary and voluntary land conversion in the current laws and policies, and the implementation of these laws, and to propose improvements to be considered in the preparation of the law on amendments and supplementations of the Land Law scheduled to be placed before the National Assembly in 2013.